Hubungan Stigma Diri Dengan Kualitas Hidup Pasien Skizofrenia - Sarsilah Sarsilah; Marisca Agustina; Irma Herliana (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Schizophrenia is a chronic and severe brain disease that affects a person's thoughts, feelings and behavior. The core symptoms of schizophrenia can be categorized into five groups, namely positive symptoms, negative symptoms, cognitive symptoms, emotional symptoms, and social/occupational dysfunction. The aim of this study was to determine the relationship between self-stigma and quality of life in schizophrenia patients. This research uses a descriptive correlation design applied cross-sectionally. The population in the study were schizophrenic patients at the Dr. Mental Hospital. Soeharto Heerdjan Jakarta as many as 106 people. Sample calculations used the Slovin formula to obtain a sample size of 84 respondents. The sampling technique uses purposive sampling. Test the hypothesis in research using Chi-square. The results of the chi-square statistical test obtained a p value of 0.001, which means the p-value is smaller than alpha (0.05). Therefore, the null hypothesis is rejected and the alternative hypothesis is accepted, or there is a relationship between self-stigma and the quality of life of schizophrenia patients in mental hospitals. The results of the study showed that the odds ratio (OR) of self-stigma having a negative impact on a decent quality of life in people with schizophrenia was 0.393. In conclusion, there is a relationship between self-stigma and quality of life in schizophrenia patients.